A Consensus for Classification and Pathologic Reporting of Pseudomyxoma Peritonei and Associated Appendiceal Neoplasia: The Results of the Peritoneal Surface Oncology Group International (PSOGI) Modified Delphi Process. (January 2016) - Carr, Norman J.; Cecil, Thomas D.; Mohamed, Faheez; Sobin, Leslie H.; Sugarbaker, Paul H.; González-Moreno, Santiago; Taflampas, Panos; Chapman, Sara; Moran, Brendan J.
Abstract : Pseudomyxoma peritonei (PMP) is a complex disease with unique biological behavior that usually arises from appendiceal mucinous neoplasia. The classification of PMP and its primary appendiceal neoplasia is contentious, and an international modified Delphi consensus process was instigated to address terminology and definitions. A classification of mucinous appendiceal neoplasia was developed, and it was agreed that "mucinous adenocarcinoma" should be reserved for lesions with infiltrative invasion. The term "low-grade appendiceal mucinous neoplasm" was supported and it was agreed that "cystadenoma" should no longer be recommended. A new term of "high-grade appendiceal mucinous neoplasm" was proposed for lesions without infiltrative invasion but with high-grade cytologic atypia. Serrated polyp with or without dysplasia was preferred for tumors with serrated features confined to the mucosa with an intact muscularis mucosae. Consensus was achieved on the pathologic classification of PMP, defined as the intraperitoneal accumulation of mucus due to mucinous neoplasia characterized by the redistribution phenomenon. Three categories of PMP were agreed—low grade, high grade, and high grade with signet ring cells. Acellular mucin should be classified separately. It was agreed that low-grade and high-grade mucinous carcinoma peritonei should be considered synonymous with disseminated peritoneal adenomucinosis and peritoneal mucinous carcinomatosis, respectively. A checklist for the pathologic reporting of PMP and appendiceal mucinous neoplasms was also developed. By adopting the classifications and definitions that were agreed, different centers will be able to use uniform terminology that will allow meaningful comparison of their results.